1993
DOI: 10.1017/s0022112093000266
|View full text |Cite
|
Sign up to set email alerts
|

Mixed mode convection in an inclined slot

Abstract: Nonlinear interaction between transverse disturbances and longitudinal rolls has been investigated for flow in an inclined slot with a heated lower wall when both modes of instability occur at nearly the same value of the control parameter. This condition is shown to be possible for a fluid with Prandtl number greater than 0.263 897, For slightly supercritical values of the Rayleigh number (R) when the critical Rayleigh number for longitudinal rolls RLC is somewhat less than that for transverse stationary roll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…In general, the codimension 2 point γ = γ c2 , where the critical Rayleigh numbers R l c (γ) of the longitudinal rolls and R t c (γ) of the transverse ones are equal, moves continuously towards γ = 0 for decreasing Pr . Below Pr < 0.264 (more precisely calculated in Fujimura & Kelly (1992)), only the primary bifurcation to transverse rolls prevails even at incremental inclinations from the flat γ = 0 state.…”
Section: C1 Linear Stability Results For Small and Large Prmentioning
confidence: 91%
“…In general, the codimension 2 point γ = γ c2 , where the critical Rayleigh numbers R l c (γ) of the longitudinal rolls and R t c (γ) of the transverse ones are equal, moves continuously towards γ = 0 for decreasing Pr . Below Pr < 0.264 (more precisely calculated in Fujimura & Kelly (1992)), only the primary bifurcation to transverse rolls prevails even at incremental inclinations from the flat γ = 0 state.…”
Section: C1 Linear Stability Results For Small and Large Prmentioning
confidence: 91%
“…For 0 • ≤ θ 77.5 • we observed longitudinal rolls, subharmonic oscillations, Busse oscillations, undulation chaos, and crawling rolls. In the neighborhood of the codimension two point [11] for thermal and shear driven instability (77.5 • θ 84 • ), we observed drifting bimodals, drifting transverse rolls, and localized longitudinal and transverse bursts. For inclinations θ 84 • we found drifting transverse rolls, switching diamondpanes, and longitudinal bursts.…”
mentioning
confidence: 77%
“…Above a critical angle θ c ( 90 • ) the shear flow causes a primary instability to transverse rolls (TR) with roll-axes perpendicular to the shear flow [7]. The few prior experiments [8-10] on ILC showed reasonable agreement with the linear theory [7,[11][12][13]. These experiments also demonstrated that LR are unstable to some form of undulations [8][9][10], in qualitative agreement with theory [12,13], but the quantitative details of the state were inaccessible due to experimental limitations.Here we report the first experimental results on pattern formation in ILC for large aspectratio systems in a range of inclination angles 0 • ≤ θ ≤ 120 • , i.e., from horizontal (heated from below) to past vertical (heated from above).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…, the component of gravity tangential to the fluid layer will cause buoyant fluid to flow up along the warm wall and down along the cold wall. This shear flow, in turn, tends to break the in-plane isotropy of the usual horizontal layer heated from below, causing a departure of the dynamics from well-known RB mechanisms (Chen and Pearlstein[72]; Fujimura and Kelly[73]; Kaloni and Qiao[74]). For <0, the higher the absolute value of , the less important the contribution of the shear flow is, until for  = -90° classical RB convection isrecovered.…”
mentioning
confidence: 99%